(untitled) (SCIÉNDO INGENIUM, 2023)
When there is a conventional freezing, the reticular tissue of the asparagus is deteriorated, due to the expansion of the water when it turns into ice, and does not maintain the flavor and texture of fresh asparagus. The present work consisted of freezing white asparagus from the same lot, simultaneously, by an electromagnetic wave-assisted method and by the conventional method, which consisted of reaching the freezing temperature, without any control. The asparagus shoots were subjected to freezing temperatures between -5 to -25 °C in 35 minutes, in the two methods, the traditional and the one proposed by this work as recommended by ABI Corporation, manufacturer of the live cell freezing equipment, using electromagnetic waves (Cells Alive System (CAS)), after which they were stored frozen for one year and subjected to chromatographic and electron microscopy analysis from the second month, obtaining results that show advantages of the use of electromagnetic waves in freezing. Electron microscopy was used to determine the difference in the internal molecular structure of the asparagus frozen by both methods, showing a greater molecular deterioration in the conventionally frozen asparagus.